Characterization of the malaria parasite Plasmodium falciparum Tepsin homolog - Stéphanie Roucheray; Maria R. Narciso; Dave Richard (Microbiology Spectrum)
ABSTRACT Plasmodium parasites rely on the invasion of human erythrocytes for their survival. This invasion process is facilitated by specialized organelles (rhoptry, micronemes, and dense granules) housed within a distinctive structure known as the apical complex. How the apical complex is generated is still enigmatic, especially how specificity is achieved in the vesicular trafficking between the Golgi apparatus and the apical organelles, but phosphoinositide lipids might potentially be involved. Here, we describe the characterization of a putative phosphoinositide-binding protein containing an Epsin NH2-terminal homology (ENTH) domain, Pf3D7_1459600. We show that this protein is structurally homologous to human Tepsin. Surprisingly, unlike other Tepsins, the ENTH domain of PfTepsin binds non-specifically to phosphoinositides in vitro, potentially through a positively charged pocket. Colocalization assays revealed that PfTepsin potentially transits between the Golgi apparatus and some of the apical organelles in developing schizonts. Finally, we provide evidence that PfTepsin potentially interacts with members of the clathrin and adaptor protein 4 complexes.IMPORTANCEMalaria takes an enormous toll on affected societies, and new drugs are urgently required. Understanding how the parasite causing malaria replicates could lead to potential new drug targets. Our work characterizes a protein called Tepsin that could potentially be important for the parasite to generate organelles critical for its survival.